Retrospective study of the outcomes of necrotizing fasciitis in intensive care unit, Hospital Raja Perempuan Zainab II, Kota Bharu, Kelantan - Mustapa, Noor Shazlini (2016)
Background: Necrotizing fasciitis is a rapidly progressive soft tissue infection involving deep fascia which carries relatively high mortality rate worldwide. The aim of this study is to determine the mortality rate in our local general hospital and to investigate the factors that determine the primary outcome (mortality) of the necrotizing fasciitis patients treated in Intensive Care Unit. Methods: This is retrospective cross sectional study involved 71 patients admitted to intensive care unit (ICU) HRPZ II from January 2012 to December 2015. Patients were analyzed for presence of co-morbidities, Acute Physiology and Chronic Health Evaluation (APACHE II score), factors important in pathogenesis and treatment, and mortality. Results: The overall mortality was 22/71(31%). The mean APACHE II score was 19.2 (SD=6.57) and the median time to operation was 50 hours (IQR=70.0). Factors directly contributing towards mortality were higher APACHE II score (adjusted OR 1.41, 95%CI: 1.20, 1.66, P< 0.001) and an increase in time to surgical debridement (adjusted OR 1.03, 95%CI: 1.01, 1.05, P=0.003) Conclusion: Early surgical debridement was crucial in the treating the necrotizing fasciitis. High APACHE 11 score during admission was associated with increase mortality.